Effectiveness of adjuvant trastuzumab in daily clinical practice - Matos, Erika (Radiology and oncology (Ljubljana), 2014)
Background. Human epidermal growth factor receptor 2 (HER2) positive breast cancer is an entity with aggressive behaviour. One year of adjuvant trastuzumab significantly improves the disease free survival in the range of 40-50% and reduces the risk of dying from HER2 positive breast cancer by one third. Adjuvant treatment with trastuzumab became available in Slovenia in 2005 and the aim of this study is to explore, if the exceptional results reported in adjuvant clinical trials are achieved also in daily clinical practice. Patients and methods. An analysis of tumour and patient characteristics, type of treatment and outcome (relapse free and overall survival) of 313 patients (median age 52 years) treated at the Institute of Oncology Ljubljana in years 2005-2009 was performed. Results. Median follow-up was 4.4 years. Sixty-one patients relapsed and 24 died. Three and four years relapse free survival was 84.2% and 80.8% and the overall survival was 94.4% and 92.5%, respectively. Independent prognostic factors for relapse were tumour grade (HR 2.10; 95% CI 1.07-4.14; p = 0.031) and nodal stage (HR 1.35; 1.16-1.56; p < 0.0001) and for the overall survival nodal stage only (HR 1.36; 1.05-1.78; p = 0.021). Conclusions. The outcome in patients with adjuvant trastuzumab in daily clinical practice, treated by medical oncologists, is comparable to results obtained in international adjuvant studies.
Keywords: adjuvant; adjuvantno zdravljenje; breast; breast cancer; clinical practice; dojke; klinična praksa; rak (medicina); trastuzumab